STUDY ON LOCAL GOVERNMENT INVESTMENT PLANNING IN REGIONAL OWNED ENTERPRISES USING BSC AND SWOT ANALYSIS - Sjamsuridjal Sjamsuridjal; Meily Surianti (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2020)
In an effort to increase regional economic growth and improve services to the community, the Regional Government of Cianjur Regency plans to increase local government investment in Perumdan Tirta Mukti Cianjur, a regional drinking water company owned by the Cianjur Regency Government. Related to the increase in capital participation, a study was conducted with the aim of i) Assessing the financial capacity of the Cianjur Regency Regional Budget on the planned allocation of funds for equity participation, ii) Analyzing the performance of Perumdan Tirta Mukti Cianjur on the plan to increase the capital participation of the Cianjur Regency Government in the BUMD, iii) Make recommendations for increasing regional equity participation. The study was conducted by analyzing regional financial capacity in the Regional Government Budget of Cianjur Regency, as well as conducting a BSC (Balance Score Card) analysis and SWOT (Strength Weakness Opportunity and Threat) analysis to assess the performance of BUMD (Perumdan Tirta Mukti Cianjur). To conduct the above study, a literature study, data collection and analysis have been carried out using the above method. From the results of the analysis it was concluded that i) Regional financial capacity which is presented in the Cianjur Regency Government Budget is still sufficiently free to carry out various development innovations, including for the addition of capital participation in the Tirta Mukti Housing, ii) The Performance of the Tirta Mukti Housing Perumdam is quite ready to add capital so that can improve drinking water services in Cianjur Regency. Based on this, it can be recommended to the Regional Government of Cianjur Regency to carry out regional capital participation in Perumdam Tirtamukti, in the framework of accelerating the fulfillment of service targets in the future. However, in the implementation of capital participation in these BUMDs, they must still follow the rules and provisions of the applicable laws and regulations, and carry out adequate supervision of the performance of these BUMDs.